PENINGKATAN MUTU UJIAN DARI PAPER BASED MENUJU COMPUTER BASED - Ferry Sudarto; Hidayati Hidayati; Ageng Setiani Rafika (CCIT Journal, 2012)
Adoption of the exam objectives in a learning process is to determine the quality of one’s learner after going through the learning process. Exams are also an evaluation of the monitoring process carried out continuously and sustainably will ultimately be able to fix the quality of education. Determination of the ever-increasing standards expected to encourage the improvement of education quality, which is the determination of educational standards is the determination of the limit value (passing score). Someone said to have passed / are competent when it has passed the limit value. In the world of Education in Higher Education Raharja for example, in order to obtain the concentration Communication and Innovative Technology (CCIT) who have exam system that v used Cisco Certified Network Associate (CCNA) Benchmarking the learning standards. But it was not as easy as expected, due to problems regarding the exams are still using paper based are not inaccordance with the standard CCNA Benchmarking using computer-based exam. Benchmarking standard exam is CCNA is a computer based exam where students can do the exam questions on a computer that random such questions, which makes each student can work on the problems at the same time but each working on different problems. In the matter of computer-based working time limits there are also questions it. In Higher Education Raharja, test is still manual (paper based) where the students are still working on the exam questions and answers contained in the paper. The concept paper based is much less effective,can not even detect students who work together when the exam. At present it has developed a new method is more effective and certainly the most can help overcome these problems. Example for computer Based exam is CCNA exam and The Test of English as a Foreign Language (TOEFL) computer based and Raharja high-standard universities. In this article also identified at least four fundamental problems concerning the concept of computerbased exam, defining test methods based computer as a new way of tackling paper based exam, and final test of is to implement a computer based on the Higher Education Raharja. Computer-based methods is very important to be developed, because its function is effective in providing quality improvement exam in Higher Education Raharja thus continues to provide ease in doing the exam students and faculty in terms of giving value to students. In addition, computer-based exam process is also well suited to the needs. It can even be said that the computer based exams can erode the operational work of approximately 80% of original work not to perform the correction process answers all students who did a paperbased exam.